(untitled) (Alternautas, 2022)
In this post I review disaster risk/reduction in Cuba, particularly in light of the devastating 2017 hurricane season. The year after Irma is, for a number of reasons, an appropriate time to revisit the practices, meanings, and politics of disaster risk in this most interesting of cases. While Puerto Rico is negotiating temporary housing, an insufficient budget for critical services, and a disruptive political dispute over the post-disaster privatisation of education, the signs from Cuba are of significant recovery and business-as-usual as it enters the next hurricane season. Further intrigue is added by the fact that Raúl Castro stepped down as Cuban leader in April 2018, ending 59 years of Castro rule. The recent thaw in relations with the US under the Obama administration—and only partially refrozen by Trump—leads us to think through what the future might hold for disaster risk in a state widely considered to be in a process of opening to global influences and markets. I should add that I have as my primary target here an understanding of disaster risk rather than political ideology. Yet, as I will show, viewing the two separately proves impossible, given the clear links between societal form and top-down planning. Viewing them in tandem helps us to consider the mutually reinforcing connections between ideology, political-institutional legitimacy, and the triumph of societal organisation over not-so-natural disasters. As Cuba moves into the post-Castro era, its approach to hurricane exposure remains emphatically exceptional to what’s become a sad Caribbean norm of destitution, debt, blame shifting, and global political ineptness. Clues in dealing with the presence of natural hazards going forward must surely be found in independent analysis, as far as is possible free from twentieth century ideological conjecture.